The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1186/1471-2458-8-351
|View full text |Cite
|
Sign up to set email alerts
|

Party package travel: alcohol use and related problems in a holiday resort: a mixed methods study

Abstract: Background: People travelling abroad tend to increase their use of alcohol and other drugs. In the present study we describe organized party activities in connection with young tourists' drinking, and the differences between young people travelling with and without organized party activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
3
13
0
1
Order By: Relevance
“…For instance, Smith and Rosenthal (1997), in their study of Australian schoolies, found that both men (75.2%) and women (59.9%) reported getting drunk most or every day or night of the schoolies' week vacation. Likewise, Hesse et al (2008) found that young tourists to party resorts consume more drugs than other young people, and Josiam et al (1998) that many American youngsters are offered the opportunity to use new drugs during spring break. However, drinking and drug abuse have been identified as key accelerators of lawlessness and violence, e.g.…”
Section: Liminality and The British Youth Culturementioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Smith and Rosenthal (1997), in their study of Australian schoolies, found that both men (75.2%) and women (59.9%) reported getting drunk most or every day or night of the schoolies' week vacation. Likewise, Hesse et al (2008) found that young tourists to party resorts consume more drugs than other young people, and Josiam et al (1998) that many American youngsters are offered the opportunity to use new drugs during spring break. However, drinking and drug abuse have been identified as key accelerators of lawlessness and violence, e.g.…”
Section: Liminality and The British Youth Culturementioning
confidence: 99%
“…However, drinking and drug abuse have been identified as key accelerators of lawlessness and violence, e.g. blackouts, accidents, rapes, personal injuries, and even sudden deaths (Bellis et al, 2000;Hesse et al, 2008). Young people when intoxicated tend to be more open to socio-sexual contact with new partners, placing themselves at a higher risk of contracting sexually transmitted diseases (Josiam et al, 1998, p.504).…”
Section: Liminality and The British Youth Culturementioning
confidence: 99%
See 3 more Smart Citations